Selective removal of As, Sb, and Se ions from multicomponent mixture by nanoparticles. Issue 8 (28th April 2016) - Wang, Si-Hong; Zhang, Jing-Dong; Piao, Ji-Shou; Li, Dong-Hao
Abstract: Abstract : In this work, the selective removal of ions from multicomponent mixtures using functionalized magnetic nanoparticles (FMNPs) was demonstrated. As, Sb, and Se ions were efficiently removed from complex mixtures, such as Rhodiola rosea extracts and influent water from the sewage treatment unit of a beer brewery. As, Sb, and Se ions could be selectively adsorbed by FMNP, as demonstrated by the inductively coupled plasma mass spectrometer analyses. We also demonstrated that Pb ions are weakly adsorbed, whereas Cu, Cd, and Zn ions cannot be adsorbed by FMNP. The complexity of the mixture did not affect the selective removal of As, Sb, and Se ions. FMNP could be recycled and used repeatedly. Magnetic separation could then be applied for the selective separation of complex mixtures, such as plant extracts, industrial wastewater, and tap water.